AUTOMATED HUMAN EMOTION RECOGNITION WITH MODIFIED CONVOLUTIONAL NEURAL NETWORK - Ramafiarisona Hajasoa Malalatiana; Rafidison Maminiaina Alphonse; Choube, Mr. Pravin R.Choube (European Journal of Research Development and Sustainability, 2021)
Human emotional detection is very useful in human-robot interaction, technical equipment domain. This paper covers a method how a Modified Convolutional Neural Network (MCNN) works to detect an emotion. The steps start with face detection followed by the emotion. The method of face and eyes detection was published in Web of Scientist: International Scientific Research Journal ISSN: 2776-0979 (Volume 2, Issue 5, May, 2021) which is one of our research results. The proposed algorithm can identify from basic emotions classification to complex one with copious emotions. It depends on the emotion model introduced as training set to define the number of emotion classes. To develop this approach, we open this paper with introduction then the method and close with conclusion